Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-24T20:06:32+01:00
5x(-3x+4y+5)+3y(2x-3y+6)-18y-25x =
-15x²+20xy+25x+6xy-9y²+18y-18y-25x=
-15x²-9y²+26xy

6x(2x+4y+3)-2y(3x-6y-8) =
12x²+24xy+18x-6xy+12y²+16y=
12x²+12y²+18xy+18x+16y

3,5(5a-3b))-(-7a+5b)=
17,5a-10,5b-7a-5b=
10,5a-15,5b
2010-02-24T20:08:45+01:00
5x(-3x+4y+5)+3y(2x-3y+6)-18y-25x =
-15x²+20xy+25x+6xy-9y²+18y-18y-25x=
-15x²-9y²+26xy

6x(2x+4y+3)-2y(3x-6y-8) =
12x²+24xy+18x-6xy+12y²+16y=
12x²+12y²+18x+16y+18xy

3,5(5a-3b)-(-7a+5b)=
17,5a-10,5b+7a-5b=
10,5a-15,5b